Keeping Citizens Engaged: A Comparison Between Online and Offline Participants. (March 2017) - Yetano, Ana; Royo, Sonia
This study analyzes whether there are any differences in enrollment and drop-out rates between e-participation and traditional participation in a long-term citizen collaboration project. The theoretical framework is based on networked individualism. Results show that capturing and maintaining citizen interest is a daunting task, even in a sensitive topic that might generate positive and tangible benefits for citizens. The higher levels of accessibility offered by information and communication technologies (ICTs) are not enough to reverse public apathy, and person-to-person contact is more effective to maintain engagement. Based on the findings, some actions to reduce dropout in long-term citizen collaboration projects are suggested.